Readers and writers in primary grades a balanced and integrated approach : K-4 - Combs, Martha (Pearson/Merrill/Prentice Hall, 2006)
"Readers and Writers in Primary Grades is organized around strategies that benefit elementary school teachers in their efforts to be responsive to the developmental literacy needs of young children. Integrating theory and practice, these strategies offer a balanced look at appropriate literacy activities for K-3 classrooms. Chapter topics include reading aloud to children, shared reading, shared and interactive writing, guided and independent reading, guided and independent writing, literature study, developing phonological awareness and a strong phonics base, integrating phonics and structure, and linking children's learning experiences with a balanced literacy program."